Handbook of Materials Modeling 2018
DOI: 10.1007/978-3-319-50257-1_120-1
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Monte Carlo Algorithms for Nuclear Materials Applications

Abstract: Microstructure evolution of irradiated materials is a complex phenomenon that involves time and length scales that can expand several orders of magnitude. Defects produced in the irradiation can interact with the existing microstructure, sometimes inducing changes in the mechanical, electrical or even magnetic properties. The selection of the most adequate material for nuclear applications requires an understanding at a fundamental level of the evolution of these defects during the lifetime of the reactors. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…This subject might not have received attention if the traditional view of large-defect dominated microstruture had persisted, illustrating the power of combining modelling with experimental analysis; this will likely prompt future combined experimental-simulation research collaborations. kMC [119,154,266,267] , along with rate theory-based approaches [121,269] , is also being used to explore evolution beyond the immediate cascade collapse timescales (several picoseconds) that MD cannot currently reach with regularity. These techniques are able to reach the time and length scales of irradiation experiments and can begin to provide understanding of the defect evolution behaviour that will occur in the harsh neutron irradiation fields of fusion reactors [155] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This subject might not have received attention if the traditional view of large-defect dominated microstruture had persisted, illustrating the power of combining modelling with experimental analysis; this will likely prompt future combined experimental-simulation research collaborations. kMC [119,154,266,267] , along with rate theory-based approaches [121,269] , is also being used to explore evolution beyond the immediate cascade collapse timescales (several picoseconds) that MD cannot currently reach with regularity. These techniques are able to reach the time and length scales of irradiation experiments and can begin to provide understanding of the defect evolution behaviour that will occur in the harsh neutron irradiation fields of fusion reactors [155] .…”
Section: Discussionmentioning
confidence: 99%
“…In this case, as mentioned above, and in others, it is necessary to make use of kMC and rate theory or cluster dynamics models. For recent descriptions of these methods see Refs [153][154][155] . The first passage, rate theory and cluster dynamics models have also been integrated into phase-field models to deal with fast one directional diffusion and the effect of defect mean fields on microstructure evolution [156][157][158] .…”
Section: Statistics Of Defects and Monte Carlo Models For Microstuctu...mentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to atomistic kinetic Monte Carlo (AKMC), which handles all atomic sites of the system, in OKMC only defects are explicitly modeled. This framework is particularly convenient to model systems containing point defects, point defect clusters and dislocations under irradiation [12,13], especially at low temperature where point defect emission by sinks (dislocations, surfaces, point defect clusters, etc) can be neglected. Indeed the migration of irradiation-induced point defects in the matrix followed by their absorption by sinks is simulated faithfully, by performing the successive atomic jumps in the matrix depending on the local stress state [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Decades of research have shown the vast potential of oxides based on the fluorite structure to fit these requirements, and a wide range of such materials has been investigated from the experimental thermodynamic perspective. In this review, we stress that common structural and thermodynamic features of nuclear materials and other fluorite oxides enable many diverse applications, for example, to thermal and environmental barrier coatings for use in terrestrial and aerospace settings, catalysis, solid oxide fuel cells, and batteries. , This review is focused on experimental thermochemistry; much less emphasis is placed on computational methods for nuclear materials for which several good reviews are available. …”
Section: Introductionmentioning
confidence: 99%